An initial study on ocean acidification in Southern waters of Vietnam - Le Hung , Phu; Vo Tran , Tuan Linh; Pham Hong, Ngoc (Vietnam Journal of Marine Science and Technology, 2021)
Ocean acidification (OA) refers to the increase of dissolved CO2 and the reduction in the pH of seawater as a consequence of the absorption of large amounts of carbon dioxide (CO2) by the oceans. This process is the result of large quantities of CO2, produced by vehicles and industrial and agricultural activities. Over the past decades there have been many worldwide studies focusing on potential impacts of OA. However, researches regarding this issue remain scarce in Vietnam. In this paper, data of pH, total alkalinity (TA), dissolved inorganic carbon (HCO3-, CO32-, CO2), partial pressure of CO2 (pCO2) and the state of aragonite saturation (Ωar) measured in Southern waters of Vietnam in 2018 were used to: (1) Provide the initial data of OA parameters in Southern waters of Vietnam; (2) Compare the current situation of OA in Southern waters of Vietnam with the situation of world oceans. The results showed that mean values of pH, TA and CO32- concentrations were 8.04 (7.92–8.11), 2300.28 µmol/kgSW (2,144.10–2,523.15), 218.83 µmol/kgSW (151.32–262.83), respectively. These values were higher in offshore areas than in coastal areas, especially at the estuaries. The average value of pCO2 was 414.47 µatm (327.93–568.59), higher when compared with that of other areas (370 µatm). On the other hand, the state of aragonite saturation of the studied area had the similar patterns of TA and CO32- concentrations. Most of values were always greater than 3, with this saturation state, the marine calcifiers are more likely to survive and reproduce.